US fiscal federalism during the COVID-19 pandemic - Jeffrey Clemens; Benedic N. Ippolito; Stan Veuger (American Enterprise Institute (AEI), 2020)
The likely impact of the COVID-19 pandemic on state and local government revenues is increasingly well understood.
Keywords: A; 330; Coronavirus; Federalism; Fiscal Policy; Medicaid; State And Local Budgets